1998
DOI: 10.1002/(sici)1097-461x(1998)70:2<303::aid-qua6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties of density functional theory in predicting the torsional potential of 2,2?-bithiophene

Abstract: ABSTRACT:The internal rotation of 2,2Ј-bithiophene was investigated within the Ž . density functional theory DFT approach. Fully optimized DFT torsional potentials are Ž . compared with Møller᎐Plesset MP2 results which predict a fourfold potential with s-cis-and s-trans-gauche minima. DFT calculations fail in describing the energetics of the internal rotation because they favor planar vs. perpendicular conformers. Gradientcorrected functionals provide torsional potentials where the gauche minima have almost va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…This seems to be connected to the fact that now we are using nonplanar geometries, which are expected to be less aromatic. 26 Although TD-B3LYP underestimates the HOMO → LUMO excitation energy and TD-M05-2X overestimates it, both methods yield results close to the experimental values. Finally, although the use of basis sets with diffuse functions are recommended for energy calculations, 27 for the systems under study no significant differences were found between the use of 6-31+ G ‫ءء‬ and 6-31G ‫ء‬ or 6-311G ‫ءء‬ basis sets.…”
Section: E Homo\ Lumo Excitation Energiesmentioning
confidence: 70%
“…This seems to be connected to the fact that now we are using nonplanar geometries, which are expected to be less aromatic. 26 Although TD-B3LYP underestimates the HOMO → LUMO excitation energy and TD-M05-2X overestimates it, both methods yield results close to the experimental values. Finally, although the use of basis sets with diffuse functions are recommended for energy calculations, 27 for the systems under study no significant differences were found between the use of 6-31+ G ‫ءء‬ and 6-31G ‫ء‬ or 6-311G ‫ءء‬ basis sets.…”
Section: E Homo\ Lumo Excitation Energiesmentioning
confidence: 70%
“…60,61 Semiconducting related properties (E LUMO , EA, λ i and t 12 ) were calculated at the B3LYP/6-31+G* level of theory. Although Koopman's theorem is not rigorously applicable to Kohn-Sham orbital energies, Perdew proved a connection between ionization potentials/electron affinities and HOMO/LUMO energies through Janak's theorem (see, e.g.…”
Section: -59mentioning
confidence: 99%
“…The excited state characteristics (exCitation energies, transition dipole integral, rotatory strengths) were determined using adiabatic approximation using a time-dependent density functional approach (TDDFT) [68] employing the B3PW91fuctional and 6-311++ G(2d,2p) basis set. The computational cost of TDDFT is roughly comparable to singleexcitation theories based on a HF ground state, such as singleexcitation configuration interaction (CIS); however, numerical applications reported so far indicate that TDDFT employing current exchange-correlation functional performs significantly better than HF-based single-excitation theories for the low-lying valence excited states of both closed shell and open-shell molecules [69][70][71][72].…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The total static dipole moment (μ), average linear polarizability (α) and first-order hyperpolarizability (β) using the x, y, z components of the compound from Gaussian 03 W [60] output were calculated by Eqs. 4-6 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%